EFFECT OF COMPETITIVE LACTIC TRAINING ON CREATINE ENZYME CONCENTRATION, PERFORMANCE ENDURANCE, AND TACTICAL BEHAVIOR IN FOOTBALL - Wathik Mohammed Abdallah (Galaxy International Interdisciplinary Research Journal, 2023)
The research aimed to study the effect of competitive lactic exercises on creatine enzyme, performance endurance and tactical behavior in football. The researcher used the experimental method in the manner of two equal groups, and the football players belonging to the Diwaniyah Sports Club participating in the Youth Football Premier League for the season (2022-2023 AD) defined their research community. They were randomly divided into two groups, experimental and control, each group consisting of (12) players, after excluding (4) players for non-regularity in training.